Pengaruh Latihan Ball Handling terhadap Peningkatan Keterampilan Dribbling Siswa dalam Pembelajaran Ekstrakurikuler - Wawan Muhammad Azlan; Muhammad Husni Tamim; Prietia Eko Wardoyo (South Sulawesi Education Development, 2026)
Dribbling ability is one of the key fundamental technical skills in basketball as it underpins ball control and player movement during a match. Within the SMK Negeri 3 Selong basketball team, players’ dribbling abilities are not yet consistent, so more specific training is required to improve ball control. This study aims to analyse the effect of ball-handling training on dribbling skills in the SMK Negeri 3 Selong basketball team. The study employed a quantitative approach using an experimental method and a pre-experimental design in the form of a One-Group Pre-test-Post-test Design. The research subjects consisted of 15 students who were members of the SMK Negeri 3 Selong basketball extracurricular team. Dribbling ability was measured before and after the ball-handling training programme, and the data were analysed using a Paired Sample T-Test with the aid of SPSS version 25. The results showed an improvement in dribbling ability, with the mean score rising from 63.73 in the pre-test to 86.06 in the post-test. The results of the Paired-Sample t-test showed a significance value of 0.000 (0.05), indicating a difference in dribbling ability before and after the ball-handling training programme. These findings suggest that ball-handling training can serve as a relevant form of technical training to support the improvement of dribbling ability among school-level basketball players.